Using Story Reading Technique to Improve EFL Young Learners' Vocabulary - Siahaan, Sri Darma (JET (Journal of English Teaching), 2012)
This study was conducted to improve young learners' English vocabulary. To attain the objective, a three-cycled action research was carried out to teach vocabularies by using the story reading technique. The participants were 10 students of the K-1 grade in Grace Kids Preschool, Jakarta. The quantitative data collected using tests were analyzed using SPSS, and the qualitative data collected using observation and interview techniques were analyzed descriptively. The results indicated that the story reading techniques improved the participants' vocabulary mastery, as shown by the increase of the mean scores of the tests conducted, i.e. 42 (in the pre-test) to 62 (post-test of Cycle I) to 80 (post-test of Cycle II), and to 92 (post-test of Cycle III). Based on the findings, it was concluded that the use of the story-reading technique was effective to improve kindergarten students' vocabulary mastery.